Formation Mechanism of Knowledge Stickiness in the Collaborative Innovation of Industry–University–Research- - Zhang Feng; Liu Guoxin (Journal of Digital Information Management, 2020)
Purpose In the context of deepening the cooperation of Industryâ€“Universityâ€“Research (IUR), enterprises must gain competitive advantage by transferring external knowledge to the enterprise for knowledge appreciation. On the basis of the knowledge stickiness encountered in the process of knowledge transfer in the collaborative innovation of IUR, the formation process and causes of knowledge stickiness are analyzed. Design/methodology/approach In this study, the knowledge flow model based on heat conduction theory was proposed. The dynamic simulation was carried out using MATLAB software. The knowledge flow and evolution process in IUR were analyzed from the macro level, whereas the role and influence of various factors in knowledge stickiness was analyzed from the micro level. Finally, the preliminary mechanism of knowledge management (sharing and transfer) between IUR was established. Findings Results show that: the process of knowledge transfer between IUR is the process of continuously realizing knowledge increment and knowledge creation, and the process of knowledge evolution between IUR is a process that the Industry, the University and the Research approach continuously; and knowledge stickiness has a direct impact on the efficiency of knowledge transfer. Strengthening the cognition between IUR, increasing the number of activities between IUR, and creating a collaborative innovation atmosphere between IUR will reduce knowledge stickiness and improve the efficiency of knowledge transfer. Originality/value: Knowledge stickiness is classified from the perspective of â€œSituationâ€“Actionâ€“Cognitionâ€ (Sâ€“ Aâ€“C) and the generation process of knowledge stickiness in knowledge transfer is explored by using heat conduction theory, which makes a positive contribution to the exploration of the internal mechanism and transfer path of knowledge stickiness.

Fault Prediction in Fuzzy Discrete Event Systems: A Diagnoser Approach- - Bilal Benmessahel; Farid Nouioua; Mohamed Touahria; Abderrahim Chariete (Journal of Digital Information Management, 2019)
In this workm we study the fault prediction in fuzzy discrete event systems. Fuzzy discrete event systems are proposed to deal with vagueness, impreciseness, and subjectivity in real-world problems. The verification is divided into two steps. In the first step, we give a method to construct a Diagnoser. And in the second step, based on the structure of diagnoser we give the necessary and sufficient conditions to verify the future occurrence of the fault. The newly proposed approach allows us to deal with the problem of fault prediction for both crisp DESs and FDESs. Finally, an example is provided to illustrate the efficiency of the proposed approach.

A Framework for Big Data Pre-processing and Search Optimization Using Hmga-aco: A Hierarchical Optimization Approach- - K. V. Rama Satish; N. P Kavya (Progress in Computing Applications, 2018)

From Words to Emoticons: Deep Emotion Recognition in Text and Its Wider Implications - Rafal Rzepka; Mitsuru Takizawa; Jordi Vallverdu; Michal Ptaszynski; Pawel Dybala; Kenji Araki (International Journal of Computational Linguistics Research, 2018)

Fusion Model for Traffic Sign Detection, Tracking and Recognition - Hubham Dhingra; Shalini Diwakar; G. Saranya; Manish Kumar (Journal of Electronic Systems, 2018)

Future Reference Sentence Extraction in Support of Future Event Prediction- - Yoko Nakajima; Michal Ptaszynski; Hirotoshi Honma; Fumito Masui (International Journal of Computational Linguistics Research, 2018)

A fast algorithm for plagiarism detection in large-scale data - Baba, K. (Journal of Digital Information Management, 2017)

A Fast Algorithm for Plagiarism Detection in Large-scale Data- - Kensuke Baba (Journal of Digital Information Management, 2017)
This paper proposes a fast plagiarism detection algorithm in large-scale data. Plagiarisms of superficial descriptions, such as “copy and paste”, can be detected using a simple document similarity based on string matching. The algorithm reduces the effort for computing the document similarity by approximating the similarity. The effects of the approximation on the processing time and accuracy are evaluated by conducting experiments with a data set generated from practical scholarly documents. The experimental results show that the algorithm based on the approximated similarity can reduce the processing time of the straightforward algorithm based on the exact similarity to less than one-third in exchange for a slight decrease of the accuracy.

Feasibility of digital forensic examination and analysis of a cloud based storage snapshot - Almulla, S.; Iraqi, Y.; Jones, A. (Journal of Digital Information Management, 2017)

Formal transformation of spatiotemporal data from object-oriented database to XML - Bai, L.; Jia, Z.; Liu, J. (Journal of Digital Information Management, 2017)

A feature selection method to handle imbalanced data in text classification - Chang, F.; Guo, J.; Xu, W.; Yao, K. (Journal of Digital Information Management, 2015)

Fair virtual bandwidth allocation model in virtual data centers - Yuan, Y.; Wang, C.-R.; Wang, C. (Journal of Digital Information Management, 2013)
Network virtualization opens a promising way to support diverse applications over a shared substrate by running multiple virtual networks. Current virtual data centers in cloud computing have flexible mechanisms to partition compute resources but provide little control over how tenants share the network. This paper proposes a utility-maximization model for bandwidth sharing between virtual networks in the same substrate network. The aim is to improve the fairness of virtual bandwidth allocation for multi tenants, especially for virtual links which share the same physical link and carry nonfriendly traffic. We first given a basic model and then proved the model can be split into many sub models which can run on each rack-switch port. In the sub model, every physical link is associated with a fairness index constraint in maximize utility calculating. The goal is to limit the differences among the bandwidth allocation of the virtual links which share the same physical link. Experimental results show that the virtual bandwidth allocation between tenants is more reasonable.
Keywords: Bandwidth allocation; Multi-tenant; Network virtualization; Virtual data centers

Fault prediction of nonlinear system using time series novelty estimation - Su, S.; Zhang, W. (Journal of Digital Information Management, 2013)
Many complex nonlinear systems have the characteristics such as difficult modeling, dangerous testing, and high cost to experiment with fault. Aim at these points, a new kind of novelty estimation method based on an on-line Least Square Support Vector Regression (LS-SVR) algorithm is presented for fault prediction of nonlinear system in this paper. Firstly, a set of characteristic token values, which represent normal state of time series at the beginning, are selected as the training data to establish the on-line LS-SVR model. Then, the output values of the on-line model are analyzed to estimate novel pattern. Once the novel pattern is affirmed, the fault of system is forecasted immediately. The proposed method needs neither the math model of system nor the fault training data and primary knowledge, and it is believed with good real-time capability. The results of simulation on Continuous Stirred Tank Reactor (CSTR) show the efficiency.
Keywords: Fault prediction; Nonlinear system; Novelty estimation; Time series

A feature points matching algorithm based on wavelet analysis - Lijun, W.; Xin, X.; Guang, X. (Journal of Digital Information Management, 2012)
In this paper, we present an application of wavelet analysis on feature points matching. Wavelet coefficients which produced by wavelet transform can best display part character of the image. Through the new feature description and feature matching method, we can build a feature point database for each image and improve the efficiency of feature points matching. The experimental results show that this method is practicability, feasibility, good precision and fast speed.
Keywords: Coefficients; Feature points matching; Wavelet analysis; Weighted statistics

From a system dynamics causal loop diagram to an object-role model: A stepwise approach - Tulinayo, F.P.F.; Van Bommel, P.P.; Proper, H.A.E. (Journal of Digital Information Management, 2012)
Two diagrams are most commonly used in System Dynamics (SD); Causal Loop Diagrams (CLDs) and Stock and Flow Diagrams (SFDs). CLDs are qualitative in nature while SFDs are quantitative. In this paper we draw our attention to CLDs. CLDs are visual representation of dynamic influences with inter-relationships amongst a collection of SD variables. They are used to qualitatively capture structures and interactions of feedback loops. CLDs however, have been found to be ambiguous, lack detail and not easy to conceptualize. In this paper therefore, we come up with steps on how to transfer information from a CLD into an Object Role Modeling (ORM) model. We carry out this study to improve CLD model conceptualization, make CLD variables explicit and to reduce on CLD model ambiguity. To achieve this we use ORM, a fact oriented method whose focus is on domain conceptualization through data modeling because of its conceptual focus and roots in verbalization, graphical expressiveness and well defined semantics. To apply and validate these steps, we use a case as an example in focus session setting. From these focus sessions, evaluations and discussion of results are made and finally conclusions are drawn.
Keywords: Causal loop diagram; Object role model; Object-role modeling; System dynamics

Functional requirements analysis-based method for product platform design in axiomatic design - Cheng, X. (Journal of Digital Information Management, 2012)
Today's companies are increasingly being challenged to develop platform-based product families to increase variety of products, while keeping production costs low. In order to provide effective platform-based method and systematically analyzing the customer needs on product design, the functional requirements are classified into basic functional requirements, expectable functional requirements and adjunctive functional requirements. Axiomatic design theory was applied to zigzagging mapping between functional requirements and design parameters, and a new decomposition method to link design matrix and design structure matrix was proposed based on the functional requirements. The common parameters were determined through analyzing the sensitivity of functional requirements to design parameters and the relation degree among design parameters. By way of illustration, a family of drum brake was designed and its results demonstrated the effectiveness and practical value of the method.
Keywords: Axiomatic design; Functional requirements analysis; Product platform; Relation degree

Fast remote user authentication scheme with smart card based on quadratic residue - Wu, T.-S.; Lin, H.-Y.; Lee, M.-L.; Chen, W.-Y. (Journal of Digital Information Management, 2011)
There are many kinds of online services in our daily life, such as e-mail and messenger. When we link to a remote host, we are required to login first, supplying a username and the corresponding password, and then obtain the resources or have services. Most commonly, we might use a smart card to assistant us to login a remote site. In 1981, Lamport proposed a remote authentication scheme for communication through insecure channels. Lu and Cao further proposed an efficient scheme based on quadratic residue in 2005. In the Lu-Cao scheme, it is unnecessary for the server to store the verification table. However, some obvious drawbacks are that users cannot freely choose their own passwords and their scheme is inefficient due to complex computations. In this paper, we proposed an improvement of the Lu-Cao scheme to make it more efficient and secure.
Keywords: Password authentication; Quadratic residue; Smart card; Verification table

Froglingo, a programming language empowered by a total-recursive-equivalent data model - Xu, K.; Zhang, J.; Gao, S. (Journal of Digital Information Management, 2011)
The EP (Enterprise-Participant) data model is a language homomorphic to and semantically equivalent to a class of total recursive functions. It takes a unique position in the fields of programming languages and database management. Mathematically, it enables a programming language to achieve the greatest possible ease of use in software development and maintenance. (This assumes that a programming language incorporated with a higher expressive data model was easier than another one with a lower expressive data model, or no data model at all.) Practically, Froglingo - a programming language incorporated with the EP data model is a monolith that consolidates multiple software components of traditional software architecture. In addition, Froglingo is untyped, i.e., programmers write application programs without a necessity of user-defined types. Finally, Froglingo is a novel approach to many challenges facing traditional technologies, including feature scalability, user interface flexibility, and similarity. In this paper, we show with further clarity the concept of ease of use by proposing a mathematical definition for the concept of data models and by relating Froglingo with other programming language through the analysis of types and higher-order functions.
Keywords: EP data model; Froglingo programming langauge; Higher-order functions; Knowledge management; Total-recursive equivalence

Fusion user browsing behavior and user interests autonomous control of personalized search results sort - Li, J.; Wang, H.; Guo, Y. (Journal of Digital Information Management, 2011)
Reference simplifies the ODP concept, establish a user hierarchical structure can be controlled autonomously interest preference expression of use interests model. Meanwhile, from the user's browsing behavior can reflect the user's interest in starting, this paper analyzes the relationship between the user's browsing behavior and user interest. Considering both the times of page visiting and the browsing speed for the degree of use interest, as well as the similarity of the page keywords and a single user interest point, the index can be obtained for evaluating whether a page meets the user interest preference. Utilizing it as search results of evaluation indexes, search results sorting. Further analysis under different integrity of user interests of description and different results processing under the way of sorting effect, through individual apiration is decided according to user'spersonal interest in server-side describe file integrity of, will be willing to disclosure of personal information stored in the search engine server in order to improve the quality of the search results, sensitive personal information retained in local client, reach users privacy protection effect.
Keywords: Degree of User Interest; Personalized Search; Privacy protection; Sort Search Results; User Interest Model; User's Browsing Behaviors

Fault-tolerant meta-scheduler for price-based job scheduling by applying multi-reservation method - Bouyer, A.; Abdullah, A.H. (Journal of Digital Information Management, 2010)
In market-like grids, applying an economical method for providing fault-tolerant job scheduling is necessary. Since we have to pay cost for job execution in economic grids, consumers tend to execute their jobs on a grid with minimum cost and acceptable completion time. To do this, many approaches have been proposed, but they unilaterally consider either time/cost or consumer/provider profit. Based on current research, a new approach has been proposed; the approach is an optimized, fault-tolerant method for meta-scheduler that considers bilateral satisfaction for consumer/provider and a tolerable completion time. We suppose that, if one of the provider nodes fails, there would not be enough time to start a task on a new node from the beginning. The experimental results show a promising improvement in job scheduling with less computation cost, better fault-tolerance, and an acceptable completion time.
Keywords: Check-pointing; Fault tolerance; Replication; Rough set

File replication method based on demand forecasting of file download in P2P networks - Kobayashi, M.; Kageyama, J.; Shibusawa, S.; Yonekura, T. (Journal of Digital Information Management, 2010)
In peer-to-peer (P2P) networks that support file-sharing services, the level of access demand can vary widely between different files. Since fewer nodes store files for which there is a lower demand, these files are more likely to be lost from the P2P networks if users leave the network or delete the files. File loss can cause users to seek alternatives to P2P services, and lead to degradation in service quality. We propose and evaluate a replication method based on demand forecasting that aims to prevent the loss of low-demand files. In this method, the number of file replicas to be placed is determined based on the forecast demand for the file, so that the loss of low-demand files is likely prevented by placing replicas at nodes that frequently use P2P services. Based on simulation results, we compared our proposed method with basic replication methods in terms of the number of files and the amount of storage used. Our experimental results show that the proposed method prevents file loss by preserving lowdemand files over extended periods of time. We also confirmed that the node storage resources consumed by this method are efficiently used.
Keywords: P2P file sharing; P2P networks; Replication

A framework for enhancing non context-driven XML search - Taha, K.; Elmasri, R. (Journal of Digital Information Management, 2010)
A data element specifies one of the characteristics of its parent element. Therefore, the context of a data element is determined by its parent. Non context driven search engines build relationships between data nodes based solely on their labels and proximity to one another while overlooking their contexts. Therefore, they may return faulty answers. This paper investigates the pitfalls and limitations of non context-driven XML search engines, which caused by overlooking elements' contexts. We propose a generic context-driven search framework, which could be used as a layer on top of the frameworks of non context-driven search systems.
Keywords: Contextdriven search system; Keyword search; XML; XML search engine

Framework for mixed entity resolving system using unsupervised clustering - On, B.-W.; Lee, I. (Journal of Digital Information Management, 2010)
During web search, confusion can happen due to homonym when users use non-unique values as a search term of an entity. Especially, when parts of names of an entity were used as its identifier, we call a mixed entity resolution problem whose goal is to clear out the erroneous entities. For example, if only last name is used as an identifier, we cannot distinguish "Vannessa Bush" from "George Bush." Mixed entity resolution problem is common among Web pages data. In this paper, to resolve aforementioned mixed entities on the Web, we propose a prototypical system which includes a web service based interface, unsupervised clustering scheme, and cluster ranking algorithms. In particular, since the correct number of clusters is often unknown, we study a state-of-the-art unsupervised clustering solution based on propagation of pairwise similarities of entities. Experimental results show that our approach outperforms main competing solution.
Keywords: Mixed entity resolution; Unsupervised clustering

A fuzzy grassroots ontology for improving weblog extraction - Portmann, E.; Meier, A. (Journal of Digital Information Management, 2010)
This paper presents fuzzy clustering algorithms to establish a grassroots ontology - a machine-generated weak ontology - based on folksonomies. Furthermore, it describes a search engine for vaguely associated terms and aggregates them into several meaningful cluster categories, based on the introduced weak grassroots ontology. A potential application of this ontology, weblog extraction, is illustrated using a simple example. Added value and possible future studies are discussed in the conclusion.
Keywords: Fuzzy data clustering; Information retrieval; Ontology; Search engine; Semantic web; Weblog

A forum-based organizational memory as organizational learning support - Leblanc, A.; Abel, M.-H. (Journal of Digital Information Management, 2008)
Information and Communication Technologies have transformed the way people work and have a growing impact on long life learning. Organizational Learning is an increasingly important area of research that concerns the way organizations learn and thus augment their competitive advantage, innovativeness, and effectiveness. Within the project MEMORAe2.0, we are interested by the capitalization of knowledge in the context of an organization and by organizational learning. We developed the EMEMORAe2.0 environment which is based on the concept of learning organizational memory. In this paper, we present the organizational learning approach; we stress the role of an organizational memory in this approach; we define the concept of learning organizational memory; and we specify the use of a forum concept in such a context. Then we present the approach MEMORAe, the environment E-MEMORAe2.0 we developed and its evaluation.
Keywords: Community of practice; Forum; Learning organizational memory; Ontology; Organizational learning

A framework for web content management system operations and maintenance - Souer, J.; Honders, P.; Versendaal, J.; Brinkkemper, S. (Journal of Digital Information Management, 2008)
Organizations increasingly utilize Web Content Management Systems (WCMS) to improve development speed, online flexibility and cost effectiveness for web applications. However, organizations lack the organizational processes and structure to effectively maintain WCMS. We propose a WCMS Process Framework for the operation and maintenance phase of Web Engineering. In this paper we elaborate on the construction of the framework. It encompasses the description of a generic IT Management framework and the inclusion of Web Content Management processes into a strategic, tactical, and operational level. The framework is validated through an expert validation consisting of three industry experts and a case study at a large Dutch telecommunications services provider. The case study substantiates our vision that the WCMS Process Framework contains a set of process descriptions that effectively supports the operations and maintenance of web applications.
Keywords: Content management; Information systems maintenance; Web application; Web content management system

From words to concepts in text mining - Al-Zahrani, S. (Journal of Digital Information Management, 2006)
In the text mining process the interface between the natural language text and content reflecting terms is essential for the successful indexing process. The traditional interfaces such as the sauri and lexicons have limitations for web content processing. The recent lexical nets have promises; but their efficiency needs to be tested. The current work measures the use of word relations specified by lexical nets in a large test bed. The results correlate with similar recent past studies as not all specified word relations in the lexical nets are semantically rich in expressing the conceptual relations between given words. The results call for applying more heuristic approaches for text mining.
Keywords: Concept indexing; Text mining; Text processing; Word relation